Exploring Arab Muslim Representation in the Plays of Wajdi Mouawad, Jose Rivera, Rajiv Joseph, Jessica Blank, and Erika Jensen in American Literature: A Cultural Reflection. - Hussein, Mohammad Abed; Benny, N. Solomon (South Asian Journal of Social Sciences and Humanities, 2025)
The Western media has produced Arab Muslim identities according to political circumstances  leading to simplified generalizations about this community (Said, 1978). Modern United States  theatre now provides platforms for complex representations that undermine mainstream  perceptions of Arab Muslims. This study analyzes how Arab Muslims are portrayed in modern  theatre through a critical evaluation of Scorched. A postcolonial analysis based on Said’s  Orientalism (1978) and Bhabha’s theory of hybridity (1994) helps this study explore how these  theatre productions counter-simplified portrayals by presenting multifaceted representations of  Arab Muslim identity. War experiences displacement and memory function as the main focus  points in the analysis when using Trauma theory (Caruth, 1996) and performance studies  (Schechner, 2013). The Siege depicts the Palestinian battle against occupation (Abu-Manneh,  2016). The author uses both comic elements and dreamlike qualities in Bengal Tiger at the  Baghdad Zoo to portray war's irrationality (Carlson, 2001). Aftermath uses the testimonies of  Iraqi refugees to show their human side by enhancing their voice presence (Blank & Jensen,  2010). This research expands the understanding of Arab Muslim portrayal in American theatre  while showing theatre as a mechanism to evaluate politics and build cross-cultural  understanding (Hughes, 2016).
Keywords: Arab Muslim Representation; Postcolonialism; Orientalism; Trauma Theory; Performance Studies